Psychology, stress, insomnia, and resilience of medical staff in China during the COVID-19 policy opening: a cross-sectional survey - Cheng, Zhen; Tao, Yuanling; Liu, Ting; He, Siyue; Chen, Yu; Sun, Li; Chen, Zongtao (Frontiers in Public Health, 2023)
Background Since 8 January 2023 China has liberalized its control of COVID-19. In a short period of time, the infection rate of COVID-19 in China has risen rapidly, which has brought a heavy burden to medical staff. This study aimed to investigate the psychological status, stress, insomnia, effort-reward imbalance, resilience, and influencing factors of medical staff in China during the period of epidemic policy liberalization. Methods This survey was conducted from 6 February to 27 March 2023 with non-random sampling. An online questionnaire survey was conducted using HADS, PSS-14, ISI, ERI, and the resilience assessment scale for medical staff. The levels of psychological, stress, insomnia, effort-reward imbalance, and resilience of medical staff during the pandemic policy opening period were measured. Results A total of 2,038 valid questionnaires were collected. 68.5% and 53.9% of medical staff had different degrees of anxiety and depression, respectively. Excessive stress, insomnia, and high effort and low reward were 40.2%, 43.2%, and 14.2%, respectively. Gender, Profession, education level, and age are important factors that lead to anxiety and depression. Women, nurses, higher education, longer working years and hours, high effort, and low reward are risk factors for the above conditions. There was a certain correlation among the five scales, among which anxiety, depression, stress, insomnia, effort-reward imbalance, and other factors were positively correlated, while resilience was negatively correlated with these factors. Conclusion This study found that anxiety, depression, stress, insomnia, and other psychological problems of medical staff in China during the policy opening period of COVID-19 were more serious than before. At the individual and organizational levels, it is necessary to improve the well-being of medical staff, optimize the allocation of human resources, and promote the mental health of medical staff with a focus on prevention and mitigation, with the entry point of improving resilience and preventing the effort-reward imbalance.